Do Children Think it is Important to Predict Learning and Behaviour Problems, and Do They Think Genetic Screening Has a Role to Play in This? - Fields, Diana; Asbury, Kathryn (Journal of Autism & Developmental Disorders, 2024)
This study explores how capable young children are of thinking about a potential future that uses DNA screening to assess an individual's likelihood of experiencing learning or behaviour difficulties. Puppets and a scenario-based approach were used to ask children aged 4–10 (n = 165) whether they thought DNA screening might be helpful or harmful. A content analysis derived six categories: (1) 'Worried about being – and being seen as – different'; (2) 'Beliefs about the origins of learning and behaviour'; (3) 'Testing is harmful'; (4) 'Testing could help'; (5) 'How soon is too soon for testing?'; and (6) 'What's the point?'. Findings indicate young children, as key stakeholders, can make useful contributions to public debate in this important and controversial area.